Bilingual education in a community language: lessons from a longitudinal study. (3rd July 2016) - Molyneux, Paul; Scull, Janet; Aliani, Renata
Abstract: Provision for students learning English as an additional language (EAL) frequently overlooks the linguistic resources these children bring to the classroom. This is despite international research that highlights the facilitative links between support of the home language and the acquisition of new languages. This article reports on a longitudinal study of Karen–English bilingual learning in the early years at one culturally and linguistically diverse primary school. It analyses classroom observation and student achievement data, work samples, staff interviews, parent questionnaires, and student self-assessments to build a rich evidence base that attests to the advantages afforded by plurilingual opportunities in what are often staunchly monolingual classroom contexts. The importance of additive language policies and pedagogies for EAL students in mainstream classes is reinforced by this study, and a framework is proposed whereby bilingual education focusing on community languages can be successfully operationalised.